A mixed-methods study exploring student nurses’ understanding of futile CPR - Batty, Emma (2014)
Abstract Background: Futile CPR has the potential to inflict significant, avoidable harms on dying patients. Futile CPR is widely debated in the literature, but there is little research into futile CPR in the context of nursing. There are no published studies exploring student nurses’ understanding of futile CPR. Aim: To explore student nurses’ understanding of futile CPR Methods: A mixed methods study, using questionnaires to establish background data and identify prominent issues. These issues were then explored in greater depth using semi-structured interviews. The interview transcripts were coded and analysed thematically. Results: Students were aware of some issues related to CPR, and felt that CPR was not compatible with a good death. However, they identified a number of factors that limited their ability to prevent futile CPR. These included a lack of support in policy for nurses’ decision making, a lack of knowledge regarding the reality of CPR and social pressures on nurses to perform CPR. Conclusions: Student nurse CPR training should address the wider sociocultural context of CPR, and provide student nurses with enough knowledge of issues related to CPR (such as survival rates) to allow them to make informed decisions and communicate these effectively with patients, relatives and staff. Attitudes influence actions, and therefore it is vital that student nurses’ attitudes towards CPR are based on accurate clinical information and reflect the reality of CPR in practice. Because very few students in this study had experienced CPR, it is vital that CPR education delivers this. There is also a need for clarification of policy to support those who feel able to identify when CPR would be inappropriate or futile, but feel pressured to perform CPR nonetheless due to fear of repercussion.